Dynamics of Electron Transfer Reaction of Trioxosulfate(IV) Ion with Dinuclear Iron(III)-Salen Complex in Perchloric Acid Medium - Atiga, Simeon; O. Ukoha, Pius; T. Ujam, Oguejiofo (Asian Journal of Chemistry, 2015)
The kinetics of oxidation of trioxosulfate(IV) ion, SO32-, by [(Fe(salen))2adi], was investigated in aqueous perchloric acid medium. Stoichiometric results indicate that one mole [(Fe(salen))2adi] was reduced per two moles SO32- oxidized. Under pseudo-first order conditions of SO32- being above 20-fold excess of concentration of the oxidant, observed rates were invariant with respect to increase in concentration. Pseudo-first order rate constants were within (1.68 ± 0.003) × 103 s-1 implying zeroth order dependence of rate on [SO32-] and first order dependence on concentration of the oxidant. The rate of reaction increased with increase in [H+], was unaffected by change in ionic strength and decreased with increase in dielectric constant of the reaction medium. Addition of small amounts of AcO- and Mg2+ ions did not catalyze the reaction. A least squares fit of rate against [H+] was linear (r2 = 0.986) and with intercept indicating that oxidation of SO32- followed two parallel paths. The reaction was analyzed on the basis of a proton-coupled outer-sphere electron transfer mechanism.